1995
DOI: 10.1038/378088a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a new cytokine that induces IFN-γ production by T cells

Abstract: The mechanism underlying the differentiation of CD4+ T cells into functionally distinct subsets (Th1 and Th2) is incompletely understood, and hitherto unidentified cytokines may be required for the functional maturation of these cells. Here we report the cloning of a recently identified IFN-gamma-inducing factor (IGIF) that augments natural killer (NK) activity in spleen cells. The gene encodes a precursor protein of 192 amino acids and a mature protein of 157 amino acids, which have no obvious similarities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
1,899
10
20

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,459 publications
(1,988 citation statements)
references
References 10 publications
39
1,899
10
20
Order By: Relevance
“…Discussion IL-18 was identified as being an IFN-g-inducing factor. Moreover, the active IL-18 protein increases IFN-g production from immune cells, such as T or NK cells, to develop Th1 cells and augment the activity of NK cells (Okamura et al, 1995). Some reports have suggested that IL-18 inhibits angiogenesis, suppresses tumor growth and enhances the anti-tumor responses (Cao et al, 1999;Ju et al, 2001).…”
Section: Il-18 Is a Critical Mediator Of Vegf-enhanced Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion IL-18 was identified as being an IFN-g-inducing factor. Moreover, the active IL-18 protein increases IFN-g production from immune cells, such as T or NK cells, to develop Th1 cells and augment the activity of NK cells (Okamura et al, 1995). Some reports have suggested that IL-18 inhibits angiogenesis, suppresses tumor growth and enhances the anti-tumor responses (Cao et al, 1999;Ju et al, 2001).…”
Section: Il-18 Is a Critical Mediator Of Vegf-enhanced Migrationmentioning
confidence: 99%
“…This active IL-18 stimulates interferon (IFN)-g production directly, which is known as the IFN-g-inducing factor. IL-18 is produced by macrophages, keratinocytes, dendritic cells as well as by tumor cells (Okamura et al, 1995;Stoll et al, 1997;Udagawa et al, 1997). It has been reported that IL-18 is involved in the immune escape of tumor cells, such as melanoma cells (Cho et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Production of this proinflammatory cytokine induces IFNg, TNFa and IL-1b secretion and enhances cytotoxic activity of NK cells. [4][5][6] A broad range of immuno-regulatory cells, including activated macrophages and dendritic cells but also stromal like cells such as keratinocytes, and osteoblasts, can produce IL-18. [7][8][9] Similar to IL-1, IL-18 is present in cells as a precursor protein, which has to be cleaved to an 18-kDa mature glycoprotein by IL-1b converting enzyme (ICE, caspase-1).…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 was first described as an (IFN-g)-inducing factor, 8 and has multiple functions including induction of the synthesis of IFN-g by T cells and natural killer (NK) cells, 8,9 promotion of Th1-type immune responses, augmentation of proliferative response and cytokine production of activated T cells. 10 Recently, it was reported that bioactive IL-18 could cause acute liver injury, 11 inflammatory arthritis, 12 allergic inflammation, 13,14 and the other autoimmune diseases, 15,16 These biologic effects of IL-18 might be implicated with the most important characteristics of AOSD, suggesting that aberrant expression of IL-18 can be related to the pathogenesis of this disease.…”
Section: Introductionmentioning
confidence: 99%